Zeraffa Giraffa (Janetta Otter-Barry Books, 2014)
This is the astonishing true story of Zeraffa, a giraffe who was sent as a gift from Egypt to France in 1826. A young boy, Atir, takes care of Zeraffa on her epic journey and the sailors sing songs as she gazes down at them. In France, Atir leads her through the countryside, and thousands of people marvel at Zeraffa. Paris falls in love with Zeraffa. The King builds her a special house in the Jardin des Plantes. On warm nights, the young princess visits, while Atir whispers stories to Zeraffa of a hot land far away. The amazing story by an award-winning author of a giraffe's extraordinary voyage from Africa to Paris